2013
DOI: 10.4161/epi.25242
|View full text |Cite
|
Sign up to set email alerts
|

Bi-PROF

Abstract: The use of next generation sequencing has expanded our view on whole mammalian methylome patterns. In particular, it provides a genome-wide insight of local DNA methylation diversity at single nucleotide level and enables the examination of single chromosome sequence sections at a sufficient statistical power. We describe a bisulfite-based sequence profiling pipeline, Bi-PROF, which is based on the 454 GS-FLX Titanium technology that allows to obtain up to one million sequence stretches at single base pair res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 9 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…Aberrations in sperm DNA methylation have also been shown to be associated with abnormalities in semen parameters (low sperm count, decreased volume of semen, reduced progressive motility, high percentage of immotile sperm lowered sperm vitality) of subfertile males that were trying to conceive for at least 10 years (Laqqan et al 2017a). The authors of this study identified that DNA methylation was consistently different at a small number of CpGs between proven fertile males and subfertile case subjects, using Infinium Human Methylation 450 K BeadChip arrays, validating previous findings using local deep bisulfite sequencing (Gries et al 2013). This study builds on earlier investigations, and recent studies by Nasri et al (2017) and Kobayashi et al (2017), showing that aberrant methylation, particularly at imprinted loci, is associated with poor-quality sperm (Marques et al 2004, Kobayashi et al 2007, Poplinski et al 2010, Pacheco et al 2011, Laurentino et al 2015.…”
Section: Dna Methylationsupporting
confidence: 85%
“…Aberrations in sperm DNA methylation have also been shown to be associated with abnormalities in semen parameters (low sperm count, decreased volume of semen, reduced progressive motility, high percentage of immotile sperm lowered sperm vitality) of subfertile males that were trying to conceive for at least 10 years (Laqqan et al 2017a). The authors of this study identified that DNA methylation was consistently different at a small number of CpGs between proven fertile males and subfertile case subjects, using Infinium Human Methylation 450 K BeadChip arrays, validating previous findings using local deep bisulfite sequencing (Gries et al 2013). This study builds on earlier investigations, and recent studies by Nasri et al (2017) and Kobayashi et al (2017), showing that aberrant methylation, particularly at imprinted loci, is associated with poor-quality sperm (Marques et al 2004, Kobayashi et al 2007, Poplinski et al 2010, Pacheco et al 2011, Laurentino et al 2015.…”
Section: Dna Methylationsupporting
confidence: 85%
“… 10 Experimental conduction was carried out as described previously 11 (details are given in Supplementary Table 2 ). SAT samples from three normal-weight and three obese participants were used (i) for selecting potentially informative CpG positions in the candidate genes using methylation data obtained from Illumina 450K BeadChip arrays and NGS-based bisulfite profiling focusing on absence of sequence polymorphism, high variability of methylation levels and association with BMI/gene expression (date not shown), and (ii) for validating SIRPH-based DNA methylation results with Bi-PROF. 12 The correlation between both methods was 0.97 ( P =0.005) for LPL -CG2, 0.87 ( P =0.024) for ADIPOQ -CG1 and 0.94 ( P =0.005) for PPARγ -CG1.…”
Section: Methodsmentioning
confidence: 91%
“…According to the results of screening study, three CpG sites that have the greatest difference in methylation level between the case and control groups were subjected to validation using local deep bisulphite sequencing (Bi-PROF) (Gries et al, 2013) according to the manufacturer's instructions. In the validation study, 136 samples (independent samples) were used and distributed as follows: 72 samples as cases and 64 samples as controls.…”
Section: Local Deep Bisulphite Profiling (Bi-prof) (Validation Study)mentioning
confidence: 99%